Nine Moral Value Messages of Shalawat Burdah in Kitab Imam Al-Bushiri - Mubarok, Muhammad Ramdan; Kosasih, Aceng; Surahman, Cucu (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2025)
Qasidah Burdah by Imam Al-Bushiri is a form of Islamic religious poetry that is full of messages and moral values. Qasidah Burdah is the right medium to spread goodness in the field of education and learning. This research examines nine moral values in Qasidah Burdah by Imam Al-Bushiri and implements them for Islamic Religious Education. This research highlights its relevance in shaping character and increasing understanding of Islamic teachings. This research design uses a qualitative approach with the type of content analysis. Primary data sources were taken from the Kitab Al-Kawakib ad-Durriyah fi Madh Khair al-Bariyyah. While secondary data is obtained from journal articles, proceedings, papers, supporting books, and valid internet sources. Then, the analysis uses the Miles and Huberman analysis technique, which includes data reduction, data presentation, and interpretation or conclusions. The analysis used is content analysis, which is then described descriptively. The results showed that Qasidah Burdah contains nine moral values, namely love for the Prophet Muhammad, tawadhu, gratitude, repentance and muhasabah, piety, compassion for others, patience and perseverance, the virtue of remembering death, and faith in the intercession of the Prophet Muhammad. This research implies that Qasidah Burdah can be a practical learning media in Islamic Religious Education to shape the character of students with noble character. Qasidah Burdah can enrich learning materials with an Islamic literary approach so that it is more interesting and relevant to increase understanding and appreciation of Islamic values.